2022
DOI: 10.1097/ta.0000000000003687
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric injury trends and relationships with social vulnerability during the COVID-19 pandemic: A multi-institutional analysis

Abstract: In this multi-institutional study of 9 Level 1 Pediatric Trauma Centers, there was an increased risk of pediatric injury during the first 6 months of the COVID-19 pandemic, with the most socially vulnerable children at greater risk of intentional injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…As we suspected, community vulnerability likely has a significant impact on firearm violence involving children. These findings are consistent with recent single-center and COVID-19 era studies that also found higher rates of pediatric firearm injuries in deprived areas 10,11,27,28 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As we suspected, community vulnerability likely has a significant impact on firearm violence involving children. These findings are consistent with recent single-center and COVID-19 era studies that also found higher rates of pediatric firearm injuries in deprived areas 10,11,27,28 …”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with recent single-center and COVID-19 era studies that also found higher rates of pediatric firearm injuries in deprived areas. 10,11,27,28 The SVI themes that had statistically significant positive associations with pediatric shooting incidents were socioeconomic status (Theme 1) and household composition and disability (Theme 2), which encompass several social factors that also had statistically significant positive associations: below poverty, lacking a high school diploma, civilian with a disability, and single-parent households. Other social factors with a statistically significant positive relationship with pediatric firearm-related injury were minority status and having no access to a vehicle.…”
Section: Discussionmentioning
confidence: 99%
“…Neither Collings nor Bessoff identified a significant change between pre- and post-SHO implementation cohorts for children that were injured by assault, SWs, or NAT, nor the intent of firearm injury (unintentional, assault, suicide, or other) [ 9 , 10 ]. Flynn-O’Brien et al found an increase in admissions and transfers for firearm, cut/pierce, and overall penetrating injuries in addition to a decrease in struck by/against and NAT injuries [ 6 , 24 ]. Crichton et al is the only study that did not find a significant increase in firearm injuries [ 25 ].…”
Section: Classifications Of Violent Injurymentioning
confidence: 99%
“…For many, this led to increased stress and social isolation, and had a negative impact on mental health [ 2 , 3 ]. Additionally, social determinants of health and socioeconomic hardship are associated with risk of violent injury and adverse health outcomes in children, and there was concern the COVID-19 pandemic exacerbated these risks [ 4 , 5 , 6 ]. Indeed, in the months and years following the start of the COVID-19 pandemic in March 2020, there were reports of an increase in pediatric violent traumatic injuries [ 3 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Existing literature is narrow in scope, mostly focusing on firearm injuries and having mixed results (Afif et al 2022 ; Collings et al 2022 ; Martin et al 2022 ; Gastineau et al 2021 ; Peña and Jena 2022 ). Other studies have assessed race/ethnicity and vulnerable population differences for the entire trauma cohort rather than by individual intents, types, and mechanisms of injury (Flynn-O’Brien et al 2022 a; Bessoff et al 2021 ; Sanford et al 2021 ; Yeates et al 2022 ). Our previous work suggested that a disparate burden of violent injuries was sustained by children of color and children living in higher vulnerability neighborhoods during the first six months of the COVID-19 pandemic (Collings et al 2022 ; Flynn-O’Brien et al 2022b ).…”
Section: Introductionmentioning
confidence: 99%